STUDENTS' MATHEMATICS POWER VIEWED FROM THE STUDENT'S CRITICAL THINKING SKILLS - Widya Ayu Pangestika; Nuqthy Faiziyah (AKSIOMA: Jurnal Program Studi Pendidikan Matematika, 2022)
This study aims to analyze students' mathematical power viewed from the students' critical thinking skills. This study was conducted at State Junior High School 3 Polokarto. The subjects of the study were determined using the snowball sampling technique. The research instrument was in the form of essay test questions and interview guidelines. The triangulation method was used as a reference to check the data. The data were analyzed using data collection, data reduction and data categorization, data presentation, and drawing conclusions. The results showed that 1) students with high critical thinking skills have good mathematical reasoning abilities with deductive mathematical reasoning models and they also have good mathematical communication and mathematical connections; 2) students with moderate critical abilities have deductive mathematical reasoning abilities with poor mathematical reasoning and mathematical communication skills, but they have good mathematical connections as e students have a longer time in understanding oral questions than written questions; and 3) students with low critical thinking skills have low mathematical deductive reasoning abilities, mathematical communication, and mathematical connections. The low students' mathematical power is caused by the difficulty in understanding the problem.